Towards understanding SFSC and the pillars of its conceptualisation: Building upon the Community of Practice approach - Petropoulou, Eugenia A.; Paschou, Maria (Frontiers in Sustainable Food Systems, 2022)
Short Food Supply Chain (SFSC) has drawn scholarly attention for its innovative features, such as the emergence of new associational forms, proximal relations and new quality conventions. A better understanding of SFSC is attained when looking at it as alternative food networks structured around organisational relationships. Aiming towards a comprehensive conceptualization of SFSC, this paper presents the findings of a transnational empirical investigation of different cases in a search of their central and most typical features. Building upon the concept of Community of Practice (CoP), SFSC are conceptualized as co-creative processes and as constructed realities with their traits being shaped by the interaction of participating multi-actors. The sample of this study involves ten CoPs which are located in different parts of Europe and which were studied through open space discussions (World Café) with the participation of the various actors involved in the chain from production to consumption, services, research and policy areas. The identification of the most typical and ubiquitous attributes of SFSC as they appear across different contexts is based on an exploratory analysis which defines the main frames of SFSC and identifies on their basis the pillars of the conceptualisation of SFSC. These pillars are sharing, authenticity and sustainability, the first one referring to the relational aspect, the second one referring to the commercialisation process and the third one relating to the rationale or underlying logic of SFSC. Given that SFSC develop as dynamic alternative networks to conventional, large scale food systems, the identified pillars signify their competitive advantage. It is envisaged that the suggested conceptualisation of SFSC would contribute to a better understanding of SFSC and foster future research on this field.